Postglacial emergence along northern Nares Strait - England, John (Meddelelser om Grønland. Geoscience, 1982)
During the last glaciation much of northern Nares Strait remained an ice-free corridor separating the northeast Ellesmere Island and northwest Greenland ice sheets. The disproportionate size of these ice sheets resulted in the lithosphere being differentially loaded on either side of this prominent rift valley. Postglacial emergence in this area is analyzed in order to determine whether glacio-isostatic unloading engendered any abnormal displacement along the Nares Strait fault zone. Present data suggest that synchronous shorelines dated 6000, 7000 and 8000 BP rise from north to south across northeast Ellesmere Island and northern Nares Strait towards the Greenland ice sheet. This is considered to represent the glacio-isostatic dominance of the Greenland ice sheet during the last glaciation together with earlier postglacial emergence towards northernmost Ellesmere Island which lay beyond the influence of the Greenland ice sheet. This Greenland dominance indicates that northeast Ellesmere Island lay in the depression marginal to the Greenland ice sheet. This, in turn, requires a lithospheric flexural parameter extending in an undisrupted manner across the Nares Strait rift valley. Hence, on a regional scale, it appears that the lithosphere in this area has integrated the depressions from these separated ice sheets without any observable unconformities along Nares Strait. Although postglacial faulting has followed initial glacio-isostatic unloading in other areas the present data base does not have the resolution to document similar events along Nares Strait.